Longitudinal tendon healing assessed with multi‐modality advanced imaging and tissue analysis. (4th August 2021) - Johnson, Sherry A.; Valdés‐Martínez, Alejandro; Turk, Philip J.; Wayne McIlwraith, Cyril; Barrett, Myra F.; McGilvray, Kirk C.; Frisbie, David D.
Abstract: Background: The range of diagnostic modalities available to evaluate superficial digital flexor tendon (SDFT) injury includes magnetic resonance imaging (MRI), computed tomography (CT) and ultrasonography (US). Direct, comprehensive comparison of multi‐modality imaging characteristics to end‐point data has not previously been performed using a model of tendinopathy but is required to obtain a better understanding of each modality's diagnostic capabilities. Objective: To compare CT, MRI and US evaluation to outcome measures for histologic, biochemical and biomechanical parameters using an equine surgical model of tendinopathy. Study design: Controlled experiment. Methods: Lesions were surgically created in both forelimb SDFTs of eight horses and imaged using MRI, CT and US at seven time points over 12 months. Imaging characteristics were then correlated to end point histologic, biochemical and biomechanical data using lasso regression. Longitudinal lesion size was compared between imaging modalities. Results: Lesion to tendon isoattenuation on CT evaluation correlated with the greatest levels of aggrecan deposition. A significant correlation between cellular density and percentage of tendon involvement on the T2‐weighted sequence and signal intensity on the proton density fat saturated (PD FS) sequence was appreciated at the 12‐month time point ( P  = .006, P  = .02 respectively). There was no significant correlation between end‐point data and US or contrast imaging characteristics. Cross sectional area lesion to tendon measurements were significantly largest on CT evaluation, followed by MRI and then US ( P  < .001). Main limitations: Experimentally induced tendon injury with singular end‐point data correlation. Conclusions: Lesion isoattenuation on CT evaluation suggested scar tissue deposition, while T2‐weighted hyperintensity indicated hypercellular tendinopathy even in chronic stages of healing. Non contrast‐enhanced MRI and CT evaluation correlated most closely to cellular characteristics of surgically damaged tendons assessed over a twelve month study period. Ultrasonographic evaluation underestimates true lesional size and should be interpreted with caution.